PENYULUHAN INTERAKSI OBAT DENGAN NUTRIEN PADA MAHASISWA FARMASI ANGKATAN 2023 UIN MALANG PENDERITA BAPILNAS - Alifia Putri (Akademi Farmasi Yamasi Makassar, 2024)
Drug and food interactions can increase or decrease the therapeutic effects of drugs. This study aims to evaluate the level of knowledge of Pharmacy students class of 2023 UIN Malang about drug interactions with nutrients in patients with cough and cold and fever. Offline and online methods were used in this study, with observation, counseling, and evaluation of respondents' level of understanding. The results showed an increase in student knowledge after counseling, indicating a positive influence of health counseling on student understanding of drug interactions with nutrients. BAPILNAS drug interaction counseling proved to have a significant effect on increasing the knowledge of Pharmacy students in the Class of 2023 UIN Malang. With the potential for drug interactions to occur at any age, this counseling is expected to prevent serious impacts on clinical outcomes. In conclusion, BAPILNAS drug interaction counseling has a significant effect on increasing the knowledge of Pharmacy students in the Class of 2023.